Neonatal Seizures: Diagnosis, Etiologies, and Management - Ziobro, Julie; Shellhaas, Renée A. (Seminars in Neurology, 2020)
Neonates are exquisitely susceptible to seizures due to several physiologic factors and combination of risks that are uniquely associated with gestation, delivery, and the immediate postnatal period. Neonatal seizures can be challenging to identify; therefore, it is imperative that clinicians have a high degree of suspicion for seizures based on the clinical history or the presence of encephalopathy with or without paroxysmal abnormal movements. Acute symptomatic neonatal seizures are due to an acute brain injury, whereas neonatal-onset epilepsy may be related to underlying structural, metabolic, or genetic disorders. Though initial, acute treatment is similar, long-term treatment and prognosis varies greatly based on underlying seizure etiology. Early identification and treatment are likely important for long-term outcomes in acute symptomatic seizures, though additional studies are needed to understand optimal seizure control metrics and the ideal duration of treatment. Advances in genetic medicine are increasingly expanding our understanding of neonatal-onset epilepsies and will continue to open doors for personalized medicine to optimize outcomes in this fragile population.
Keywords: epilepsy; neonate; encephalopathy; seizure